The Role and Significance of Correct Values in Cultivating Creativity Among University Faculty and Staff - Shukla, V K; Vairagade, Rupali (Journal of Research in Vocational Education, 2025)
The purpose of this study is to investigate the relationship between value orientation in higher education employees and their creativity. The study employed a quantitative research design from 240 employees in the higher education sector to explore these relationships. The results indicate a positive relationship between creative performance with religious, social, democratic, knowledge, hedonistic, and family prestige values. While previous studies have explored the relationship between values and performance, this research adds to the literature by specifically examining the impact on creativity, which is a crucial aspect of higher education employees' work. Furthermore, the study examines the impact of values such as family prestige and aesthetic values which have not been extensively explored in previous research. The managerial implications for organizations are that it provides the reliability of instruments that can be used to assess the value orientation and creative performance of employees.